Development of Functional Markers Associated with Phenotypic Traits for Variety Identification in Soybean - Ibarra, Mariela; Castro, Ariel; Capdevielle, Fabián (Agrociencia Uruguay, 2013)
The organization of agricultural systems requires the verification of the genetic identity and purity of cultivars. The increase in the number of soy varieties to be evaluated, and the narrow genetic base of soybean cultivars, make the identification using phenotypic descriptors very difficult. The International Union for the Protection of New Varieties of Plants (UPOV) has recognized the utility of molecular markers associated with descriptive phenotypic characteristics. With the goal of developing this kind of markers, six genic or genomic SSR were selected in silico (Sat286, Satt229, GmPrx1, GMES1173, Satt571 and GmHi), plus two previously reported markers (GmF35H and SoyF3H). All were evaluated in 35 soybean cultivars. The SSRs GmPrx1 and GmHi selected for seed coat peroxidase and hilum color respectively were monomorphic. The mean Polymorphism Information Content (PIC) value within the selected group of polymorphic markers was 0.48 with an average of 3.12 allele per locus. GmF35H discriminated the soybean varieties according to the flower color (white and purple). Discrimination tests showed a high percentage of accurate classification of growth habit (95.8%) and pubescence color (80.6%) with Sat286 and SoyF3H, respectively. The classification values for pod color (74.2%) and leaflet size (73.5%) were intermediate using GMES1173 and Satt571, respectively. The marker Satt229 was not discriminating for flowering time (50%) and maturity (42.8%). Molecular markers selected in or close to sequences of interest can be integrated into a genetic identification system as complementary markers to the classic phenotypic descriptors of soybean varieties.